1998
DOI: 10.1002/(sici)1096-9136(199805)15:5<435::aid-dia566>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia due to insulin resistance caused by interferon-γ

Abstract: Marked hyperglycaemia (30.9 mmol l −1 ) during interferon-␥ (IFN-␥) therapy for asymptomatic recurrent renal cancer as multiple lung metastases in a 52-year-old man is described. Although the involvement of IFN-␥ has been reported in the development of autoimmune diabetes, in this case, antibodies against pancreatic ␤-cells including anti-islet cell antibody (ICA) and anti-glutamic acid decarboxylase (GAD) antibody were negative. Moreover, serum level of immunoreactive insulin (IRI) (11 U ml −1 at fasting) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…The catabolic action of IFN‐γ on skeletal muscle, assessed on the basis of protein kinase activity, a myosin heavy chain content and the total protein/DNA ratio, was not supported by previous observations (Smith et al, 2007). In striking contrast, in the present study we found a marked modification of key intracellular insulin signalling pathways and protein synthesis in myogenic cells differentiated in the presence of IFN‐γ.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The catabolic action of IFN‐γ on skeletal muscle, assessed on the basis of protein kinase activity, a myosin heavy chain content and the total protein/DNA ratio, was not supported by previous observations (Smith et al, 2007). In striking contrast, in the present study we found a marked modification of key intracellular insulin signalling pathways and protein synthesis in myogenic cells differentiated in the presence of IFN‐γ.…”
Section: Discussioncontrasting
confidence: 64%
“…Such a discrepancy concerning the effect of IFN‐γ on muscle cell protein turnover could result from the experimental protocol used and/or from the differentiation state of the cells. In both studies, the action of IFN‐γ was examined in C2C12 myotubes; however, we investigated the protein synthesis and insulin signalling on the fifth day of differentiation after 5 days of cytokine treatment, whereas Smith et al (2007) described short‐term effects, with IFN‐γ treatment lasting a few hours (for assessment of the activity of signalling molecules) or 3 days (for assessment of differentiation parameters).…”
Section: Discussionmentioning
confidence: 99%
“…12 Obesity is characterized by a broad inflammatory response and many inflammatory mediators exhibit patterns of expression and/or impact insulin action that correlates with the progression of metabolic syndrome. [14][15][16][17][18] TNF-α and IL-6 expressions are enhanced in the adipose tissue in human obesity and IR. [14][15][16][17][18] TNF-α and IL-6 expressions are enhanced in the adipose tissue in human obesity and IR.…”
Section: Introductionmentioning
confidence: 99%
“…Two representative examples are the diabetogenic effect of steroids [5] and the cyclosporine-induced inhibition of insulin production by b cells [6]. However, recent findings indicate that certain proinflammatory cytokines are capable of interfering with insulin-sensitive glucose uptake and induce insulin resistance [7], as well as affecting adipose tissue metabolism [8] and modulating blood pressure [9]. Intriguingly, a member of "adipocytokine" family, TNF-a is over-expressed in the adipose tissue of obese humans [10], and contributes to insulin resistance by up-regulating free fatty acid secretion, inhibiting insulin signaling in adipocytes, and down-regulating glucose transporters [11].…”
mentioning
confidence: 99%